2003
DOI: 10.1002/cvde.200306271
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Hafnium Dioxide Thin Films by Liquid‐Injection MOCVD Using Alkylamide and Hydroxylamide Precursors

Abstract: 4 ]. Varying levels of residual carbon and nitrogen were detected in the films grown from each precursor. Analysis by X-ray diffraction (XRD) indicates that films grown from both precursors exist predominantly in the thermodynamically stable monoclinic phase. Scanning electron microscopy (SEM) shows that the morphology of the HfO 2 films from each precursor is markedly different, with films deposited from [Hf(NMe 2 ) 4 ] having a well-defined columnar crystalline structure, whereas films grown from [Hf(ONEt 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 25 publications
0
38
1
Order By: Relevance
“…[15] The 4 ). [16][17][18][19][20][21][22][23] These precursors present the advantage of containing no oxygen; however, they are so sensitive to air and humidity that they are very difficult to handle. Combination of alkoxides and alkylamides to form hafnium hydroxylamide complexes Hf(ONR 2 ) 4 are alternative possible precursors, which have been shown to be quasi eightcoordinate monomers.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[15] The 4 ). [16][17][18][19][20][21][22][23] These precursors present the advantage of containing no oxygen; however, they are so sensitive to air and humidity that they are very difficult to handle. Combination of alkoxides and alkylamides to form hafnium hydroxylamide complexes Hf(ONR 2 ) 4 are alternative possible precursors, which have been shown to be quasi eightcoordinate monomers.…”
Section: Introductionmentioning
confidence: 99%
“…Combination of alkoxides and alkylamides to form hafnium hydroxylamide complexes Hf(ONR 2 ) 4 are alternative possible precursors, which have been shown to be quasi eightcoordinate monomers. [17] The precursor Hf(ONEt 2 ) 4 has been tested for HfO 2 deposition, and compared to Hf(NMe 2 ) 4 . [17] The authors concluded that the films prepared from Hf(ONEt 2 ) 4 exhibited lower electrical properties than the films prepared from Hf(NMe 2 ) 4 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The molecular geometry can be described as elongated tetrahedral. The N-Hf-N angles within the five-member metallacycle rings (87.10 (15) [50] Hf(NMe 2 ) 3 (SiPh 2 -t Bu)(THF) (2.019(9)-2.030(9) Å), [61] and…”
Section: Precursor Syntheses and Characterizationmentioning
confidence: 99%
“…The metal nitrate complex [Hf(NO 3 ) 4 ] has been used for the MOCVD of high purity HfO 2 at low growth temperatures, [12] but anhydrous metal nitrate complexes are hazardous, highly reactive oxidants. Metal alkylamide complexes, such as [Hf(NMe 2 ) 4 ] [13,14] and [Hf(NEt 2 ) 4 ], [13] have also been used for the MOCVD of HfO 2 , but they are highly air-sensitive, and varying amounts of residual nitrogen and carbon can be incorporated in the oxide film. Metal alkoxides are attractive MOCVD precursors as they allow low deposition temperatures, and under optimum growth conditions, the deposition of low carbon-content films (<1 at.-% as measured by X-ray photoelectron spectroscopy (XPS)).…”
Section: Introductionmentioning
confidence: 99%